Molecular Detection Of Chikungunya Virus Targeting The Immunodominant Envelope (E1) Gene: Current Status And Future Applications - JAIANAND. K; RAMESH.M; GUNASEKARAN.P; SHERIFF.A.K (International Journal of Pharma and Bio Sciences, 2010)
A reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay was developed for detecting the E1 gene of Chikungunya virus (CHIKV). The RT-LAMP assay is a novel method of gene amplification that amplifies nucleic acid with high specificity, efficiency, and rapidity under isothermal conditions with a set of six specially designed primers that recognize eight distinct sequences of the target. The whole procedure is very simple and rapid, and amplification can be obtained in less than 1 h by incubating all of the reagents in a single tube with reverse transcriptase and Bst DNA polymerase at 63°C. Detection of gene amplification could be accomplished by agarose gel electrophoresis; it was found that the RT-LAMP assay demonstrated 10-fold higher sensitivity compared to RT-PCR, with a detection limit of 0.1 PFU of virus. Thus, due to easy operation without a requirement of sophisticated equipment and skilled personnel, the RT-LAMP assay reported here is a valuable tool for the rapid and real-time detection of CHIKV.